Homocysteine and other cardiovascular risk factors in patients with lichen planus. (12th December 2013) - Saleh, N.; Samir, N.; Megahed, H.; Farid, E.
Abstract Background Chronic inflammation was found to play an important role in the development of cardiovascular risk factors. Homocysteine (Hcy) and fibrinogen have been identified as a major independent risk factor for cardiovascular disease. Lichen planus is assumed to be closely related to dyslipidaemia. Several cytokines involved in lichen planus pathogenesis, could explain its association with dyslipidaemia. Also chronic inflammation with lichen planus has been suggested as a component of the metabolic syndrome. Objective The aim of this study was to detect a panel of cardiovascular risk factors in patients of lichen planus. Patients and methods This study was done on 40 patients of lichen planus and 40 healthy controls. All patients and controls were subjected to clinical examination. Serum levels of homocysteine, fibrinogen and high‐sensitive C‐reactive protein (hs‐CRP) were measured by enzyme‐linked immunosorbent assay technique (ELISA). Metabolic syndrome parameters including anthropometric measures, lipid profiles, blood sugar and blood pressure were studied. Results Patients with lichen planus showed significant association with metabolic syndrome parameters than controls (P < 0.001). Serum homocysteine, fibrinogen and hs‐CRP were significantly higher in lichen planus patients than controls (P < 0.001). Serum homocysteine correlated with both serum hs‐CRP and serum fibrinogen. However, there was no correlation between serum levels of homocysteine and fibrinogen with any metabolic syndrome criteria and related disorders except for a negative correlation of fibrinogen with high‐density lipoprotein (HDL). Conclusion In the present work, patients with lichen planus were found to have higher makers of both metabolic and cardiovascular risk factors in relation to controls most probably due to long standing inflammation.